Emergency Government of Lampung Residency during Kraai Operation, 1949-1950 - Pratama, Rinaldo Adi; Maskun, Maskun; Arif, Suparman (History Department, Semarang State University and Historian Society of Indonesia, 2023)
During the independence war of Indonesia, particularly, Kraai Operation or in the military base, also known as the Dutch Military Aggression II in the Lampung Residency, made many contributions to maintaining state sovereignty. The revolution in the Lampung region was part of the Sumatra Province, namely the Lampung Residency. This study aimed to find out the impact of the Kraai Operation. The research used historical research methods. We conducted the research in three regions once the Lampung Residency’s emergency capital focused on politics, the military, and economics. During the Kraai Operation period or Dutch Military Aggression II 1949-1950, Lampung Residency led by Gele Harun Nasution issued political, military, and economic policies to counteract the Kraai Operation. He moved the Government and Defense, formed the North Front, Central Front, and Southern Front, and coordinated the camps in the Lampung Residency. Moreover, he printed emergency money for the Residency of Lampung to prevent the spread of the Dutch currency, which affected inflation.Keywords: Lampung Residency; Emergency Government; Kraai Operation; Gele Harun Nasution; Revolution Selama perang kemerdekaan Indonesia, khususnya Operasi Kraai atau Agresi Militer Belanda II, Karesidenan Lampung banyak memberikan kontribusi untuk menjaga kedaulatan negara. Penelitian ini bertujuan untuk mengetahui dampak dari Operasi Kraai di wilayah Keresidenan Lampung. Penelitian ini menggunakan metode penelitian sejarah. Penelitian ini dilakukan di tiga wilayah yang pernah menjadi ibu kota darurat Karesidenan Lampung yang fokus pada bidang politik, militer, dan ekonomi. Pada masa Operasi Kraai atau Agresi Militer Belanda II 1949-1950, Karesidenan Lampung yang dipimpin oleh Gele Harun Nasution mengeluarkan tiga kebijakan yakni politik, militer, dan ekonomi untuk menangkal Operasi Kraai. Ia menggerakkan Pemerintahan dan Pertahanan, membentuk Front Utara, Front Tengah dan Front Selatan serta mengkoordinasikan kamp-kamp di Karesidenan Lampung, dan mencetak uang darurat untuk Karesidenan Lampung untuk mencegah penyebaran mata uang Belanda yang berdampak pada inflasi besar di wilayah republic.Kata Kunci: Karesidenan Lampung; Pemerintah Darurat; Operasi Kraai; Gele Harun Nasution; Revolusi